2022
DOI: 10.1038/s41598-022-20604-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the effects of winter water warming in artificial lakes on zooplankton and its environment using combined machine learning models

Abstract: This work deals with the consequences of climate warming on aquatic ecosystems. The study determined the effects of increased water temperatures in artificial lakes during winter on predicting changes in the biomass of zooplankton taxa and their environment. We applied an innovative approach to investigate the effects of winter warming on zooplankton and physico-chemical factors. We used a modelling scheme combining hierarchical clustering, eXtreme Gradient Boosting (XGBoost) and SHapley Additive exPlanations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 71 publications
(83 reference statements)
1
10
0
Order By: Relevance
“…Thus, populations of zooplankton species characterised by smaller size, lower weight and lower nutrient requirements increased in their biomass. Ejsmont-Karabin et al 44 and Kruk et al 39 also reported a positive correlation between psammophilous-epiphytic Rotifera and increased and stable water temperature in heated lakes. Other authors observed that the growth of small crustacean species was accelerated by an increase in water temperature 5,26,47,48 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, populations of zooplankton species characterised by smaller size, lower weight and lower nutrient requirements increased in their biomass. Ejsmont-Karabin et al 44 and Kruk et al 39 also reported a positive correlation between psammophilous-epiphytic Rotifera and increased and stable water temperature in heated lakes. Other authors observed that the growth of small crustacean species was accelerated by an increase in water temperature 5,26,47,48 .…”
Section: Discussionmentioning
confidence: 91%
“…in MW and 9.2°C in WW), algal blooms were less frequent and primary production was lower 39,63 . It is worth noting that the variability of water temperature in the studied reservoirs was the most important factor that distinguished these water bodies (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, the notion of explainable artificial intelligence is enjoying immense popularity now. Explainable artificial intelligence can be defined as “artificial intelligence to identify major predictors of the dependent variable”, and there are four approaches of explainable artificial intelligence at this point, i.e., random forest impurity importance, random forest permutation importance [ 20 , 21 ], machine learning accuracy importance, and Shapley additive explanations (SHAP) [ 15 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Random forest impurity importance calculates the node impurity decrease from the creation of a branch on a certain predictor.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning accuracy importance (an extension of random forest permutation importance) calculates the accuracy decrease from the exclusion of data on the predictor. The SHAP value of a predictor for a participant measures the difference between what machine learning predicts for the probability of GID with and without the predictor [ 15 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. For example, let us assume in a hypothetical figure ( Figure 1 ) that the SHAP values of diabetes (x033) for GERD have the range of (−0.05, 0.30).…”
Section: Introductionmentioning
confidence: 99%